Neonatal stridor and laryngeal cyst: Which comes first?. Issue 1 (19th January 2017) - Marseglia, Lucia; D'Angelo, Gabriella; Impellizzeri, Pietro; Salvo, Vincenzo; Catalano, Natalia; Bruno, Rocco; Galletti, Claudio; Galletti, Bruno; Galletti, Francesco; Gitto, Eloisa
Abstract : Neonatal stridor is a rare condition usually caused by laryngomalacia. Congenital laryngeal cyst represents an uncommon cause of stridor in the neonatal population and may be misinterpreted as laryngomalacia, leading to serious morbidity and mortality if diagnosis and treatment are delayed. Herein we report the case of a full‐term infant with stridor, feeding problems and failure to thrive. Initially, direct laryngoscopy diagnosed only laryngomalacia. As stridor worsened, however, and respiratory distress appeared, repeat laryngoscopy showed vallecular laryngeal cyst, visible macroscopically. The patient was successfully treated with endoscopic marsupialization. There was no evidence of recurrence at follow up after 3 months. This case highlights the importance of laryngoscopic assessment for suspected laryngeal abnormalities in infants with stridor. If symptoms worsen, endoscopy should be repeated, because congenital laryngeal cysts may not be immediately visible macroscopically.